Shared and nonshared agency for occupational goals with mothers, fathers, VIPs, and romantic partners during young adulthood - Chang, Esther S.; Shane, Jacob; Villarreal, Brandilynn; Heckhausen, Jutta (Frontiers in Psychology, 2022)
This study applied a framework of shared and nonshared agency (Chang et al., 2010) to investigate how social partners can help and hinder young adults' career development. We also considered the extent to which motivational control could be promoted or burdened when young people seek help and encouragement from others in their careers. Based on the importance of shared agency in life goal pursuit, it was hypothesized that shared agency (i.e., perceived support and collaboration) with mothers, fathers, important adults, and romantic partners would have direct and positive associations with young adults’ career satisfaction and exploration and positive indirect associations on career development via motivational control. We further hypothesized that nonshared agency (i.e., directing and uninvolvement) would have direct and negative effects on career satisfaction and exploration and negative indirect effects on career development via motivational strategies. Results indicated that relationships can facilitate career development but differently depending upon relationship type. We found that support and directing from mothers and VIPs had positive associations with outcomes via individual motivational control whereas a total effect of collaboration with fathers and romantic partners were associated with outcomes without an indirect effect via motivational control. These findings are discussed within the context of previous socialization research and theory.